The Great Recession: on the Ineffectiveness of Domestic Policies and the Need of Multilateral Arrangements - Rojas, Jorge (2015)
The Great Recession is the manifestation of some fundamental problems in the real sector of the global economy, related basically to the loss of competitiveness of the U.S. and other central economies, reflected in continuous external disequilibria in the form of parallel current account deficits and financial account surpluses. Domestic monetary and fiscal (or domestic adjustment) policies have not reached a solution to the problem because we are now dealing with a global problem that requires multilateral solutions seeking to adjust some fundamental relative prices and the closing of some key structural imbalances in order to make a sustainable recovery possible. Besides, the difficulties in finding and engineering a solution show the need to reassess the theoretical paradigms underlying the economic policies that preceded the current crisis (e.g., supply-side economics).